Pengaruh kualitas pelayanan dan kepuasan anggota terhadap loyalitas anggota pada Lembaga Keuangan Baitul Maal Wat Tamwil (BMT) Indragiri di Kabupaten Indragiri Hulu - Ayu Kartika; Rosmayani Rosmayani; Ujang Paman (SYNERGY: Jurnal Bisnis dan Manajemen, 2021)
This study aims to determine the effect of service quality and member satisfaction on member loyalty at the Baitul Maal Wat Tamwil Indragiri Financial Institution. The analysis method used in this research is Data Quality Test, Multiple Linear Regression Analysis, Hypothesis Test and Classical Assumption Test. In this study, it can be concluded that the quality of services provided and the satisfaction obtained by members of the Indragiri BMT Financial Institution can generate Member Loyalty and become a value for members to always survive and be loyal to the Financial Institutions BMT Indragiri. From testing the results of data analysis in this study, the data quality test results obtained from the validity and reliability tests on the variable service quality, member satisfaction and member loyalty declared valid and reliable, as evidenced by the validity test which shows that each item value is greater than the rtabel value. 0.208. Whereas the reliability test proves that the data is reliable with 20 instrument values which state the value is greater than the r table. The results of multiple linear regression analysis between service quality, member satisfaction and member loyalty obtained the value of Y == 4,541+ 0.109X1 + 0.243X2. From the research results obtained R2 value of 0.221, which means that the variable service quality, member satisfaction has a positive and significant simultaneous influencer of 22.1% of members on member loyalty. In testing the hypothesis, namely the F test, it can be seen that together these three variables had a positive and significant simultaneous effect because the value of Fcount lebih dari Ftable (12,203 lebih dari3,10). In the t test, to test the effect of the three variables, namely service quality and member satisfaction, the service quality variables had the most dominant influence on member loyalty. Where, the count value of the service quality variable (X1) is the largest compared to the member satisfaction variable, which is 3,902.